Sloterdijk: Secretos bizarros de Freud, discretas obsesiones telecomunicativas y primeras formaciones de psicología profunda europeas - Vásquez Rocca, Adolfo (Nómadas. Critical Journal of Social and Juridical Science, 2011)
Following the plan outlined in the trilogy Spheres anthropological constitution of communications. All media history is a history of transfers of thoughts. Humans stirred up a concert of becoming links themselves creative influences multiple operators. So that the sixteenth century Europeans call magología is a man's actions mentally and spiritually open to the world that is brought to cooperate with discrete actions and reciprocal effects between things in a highly communicative world. Discrete telecommunicative obsessions that had attracted the attention of Freud, but that the creator of psychoanalysis - as Sloterdijk - wisely, kept secret to avoid making loud proclamations, he knew he would have been fatal to the scientific and clinical fate of the psychoanalytic movement that he were involved in a cultural battle between communication patterns and models hidden-archaic-illustrated. He was aware that the fate of psychoanalysis as a scientific discipline that deals with close relationships in a specifically modern epistemological framework, was alone in his alliance with the Enlightenment, it is routed by the sure path of science, occult or hiding any past magológico as mesmerism, so all this long history of participatory effects preverbal would become the bizarre secrets of the original analysis.
Keywords: Spheres; means; transference; mind; globalisation; thought; metaphysics; telecommunications; neurolinguistics